2007
DOI: 10.1103/physrevlett.99.016403
|View full text |Cite
|
Sign up to set email alerts
|

Light Quasiparticles Dominate Electronic Transport in Molecular Crystal Field-Effect Transistors

Abstract: We report on an infrared spectroscopy study of mobile holes in the accumulation layer of organic field-effect transistors based on rubrene single crystals. Our data indicate that both transport and infrared properties of these transistors at room temperature are governed by light quasiparticles in molecular orbital bands with the effective masses m* comparable to free electron mass. Furthermore, the m* values inferred from our experiments are in agreement with those determined from band structure calculations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
105
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 20 publications
(33 reference statements)
23
105
1
Order By: Relevance
“…Despite the experimental difficulties, there have been several reports of the optical conductivity of excess carriers in rubrene. Measurements by different groups [37,38,24] agree in showing a markedly non-Drude behavior at room temperature: the optical conductivity exhibits a finite frequency maximum in the far infra-red range, indicating a breakdown of semiclassical behavior, which has been ascribed to some form of localization of the charge carriers. [38] We will come back to this crucial observation in Sec.…”
Section: Experimental Overviewmentioning
confidence: 81%
“…Despite the experimental difficulties, there have been several reports of the optical conductivity of excess carriers in rubrene. Measurements by different groups [37,38,24] agree in showing a markedly non-Drude behavior at room temperature: the optical conductivity exhibits a finite frequency maximum in the far infra-red range, indicating a breakdown of semiclassical behavior, which has been ascribed to some form of localization of the charge carriers. [38] We will come back to this crucial observation in Sec.…”
Section: Experimental Overviewmentioning
confidence: 81%
“…In our analysis of these multilayer structures, we followed the protocol detailed in ref. 27. Specifically, we carried out reflection, transmission and ellipsometric measurements on the Si substrates and SiO 2 /Si wafers used in our devices and thus obtained the optical constants of layers 2 and 4.…”
Section: Extracting the Optical Constants Of Graphenementioning
confidence: 99%
“…1. Finally, we used a multi-oscillator fitting procedure 27 to account for the contribution of σ(ω) of graphene to the reflectance and transmission spectra shown in Fig. 1 using standard methods for multilayered structures.…”
Section: Extracting the Optical Constants Of Graphenementioning
confidence: 99%
“…[5][6][7][8][9] In analogy to inorganic semiconductors, this has been interpreted as an indication of delocalized charge carriers and a "bandlike" transport mechanism. [10][11][12][13] Theoretical models based on polaronic band conduction 14 indeed provide a good qualitative description of the bandlike mobility of charge carriers in pentacene, but the factors determining the absolute charge mobility remain unknown. For instance, an analysis of the high temperature mobility has indicated that the mean free path of charge carriers is of the same magnitude as the intermolecular distance.…”
mentioning
confidence: 99%